PENGARUH KINERJA PEGAWAI TERHADAP PENYELENGGARAAN DIKLAT DI PUSAT PELATIHAN MANAJEMEN DAN KEPEMIMPINAN PERTANIAN (PPMKP) CIAWI BOGOR - Pratama, Herdiansyah Ananda; S Zenju, Nandang; Purnamasari, Irma (JURNAL GOVERNANSI, 2016)
This research is focused on the impact of employeeâs performace against the training administration held by The Management and Leadership Training Center for Agriculture (PPMKP) Ciawi, Bogor, because based on the observation on the field, employeeâs performance and training implementation are not yet optimized. The purposes of this study are: (1) To know the employees of PPMKPâs performance, (2) To know how the PPMKP administered the training, (3) To assess if there is any impact on employeeâs performance against the training held by PPMKP. The type of research used is quantitative research with associative and descriptive methods. Purposive Sampling is the technique used involving 68 PPMKP employees as sample. The data gathering used was the study of literature and the study of field. To find out the employeeâs performances and training administration, analyses descriptive is applied with the result of 4,37 for performance which is in very good category with the lowest value is derived from the indicator expertise in completing the task. Whereas administration of trainingâs result score of 4,39 which is in very good categoty with the lowest score is derived from the curriculum indicator. To determine the impact on the employeeâs performance of training administration the spearman rank correlation is used, with a correlation coefficient of 0,037 and a significance value of 0,766 with positive direction and not significant, meaning thet there is a very low impact on the performance by having training.Â  The conclusion of the research shows that, (1) employeeâs performance has been very good with the lowest score is in in the indicator of realibility in completing task, (2) training administration has been very good with the lowest score is in the indicator of curriculum, also (3) there is very low impact on employeeâs performance against the trining administration. The possible suggestions made are: first, the expertise of emloyees in completing the task enhanced by giving trainings and study permits for their employees; second, curriculum plan is expected to be more adjustable with the participants by learning more on the participants background; third, research is carried out on other factors that influence the training administration, in order to see the effect on the level of training.Â Key words: performance, training administration.